Pain management in Internal Medicine and effects of a standardised educational intervention: the FADOI‐DOMINO Study. Issue 1 (6th October 2014) - Civardi, G.; Zucco, F.; Valerio, A.; Fontanella, A.; Alessandri, M.; Ciannamea, C. D.; Perale, L.; Gussoni, G.; Bonizzoni, E.; Vescovo, G.; Agnelli, G.; Campanini, M.; et al.
Summary Purpose Few real‐world data are available on the frequency and management of pain in Internal Medicine (IM). Aims of our study were to assess the prevalence of pain in IM, and to evaluate the effects on pain management of a standardised educational programme. Materials and methods The study was performed in 26 IM Units in Italy, with two cross‐sectional surveys (PRE phase and POST phase) interspersed with an educational programme. In PRE phase each Centre reviewed the hospital charts of the last 100 consecutive patients hospitalised for any cause. An educational programme was conducted in each Centre by means of the 'outreach visit', a face‐to‐face meeting between health personnel and a trained external expert. Six months after, each Centre repeated the data collection (POST phase), specular to the PRE. Results A total of 5200 medical charts were analysed. Pain was documented in 37.5% of the patients. After the educational intervention, the intensity of pain was appropriately assessed in a higher percentage of patients (77.4% vs. 47.8%, p = 0.0001), and it was more frequently monitored during hospitalisation. Qualitative definition of pain (pathogenesis, duration, etc.) increased in POST phase (75.4% vs. 62.7%, p = 0.0001). A 73.3% increase in the use of strong opioids was detected following educational programme. Conclusions Pain affects 4 out of 10 patients hospitalised in IM. According to our large real‐world study, to implement a standardised one‐shot educational programme may persistently improve the attitude of health personnel towards the characterisation and management of pain.